ESMO Precision Oncology Working Group recommendations on the structure and quality indicators for molecular tumour boards in clinical practice - Westphalen, Christoph Benedikt; Boscolo Bielo, L.; Aftimos, P.; Beltran, H.; Benary, M.; Chakravarty, D.; Collienne, Maike; Dienstmann, R.; El Helali, A.; Gainor, J.; Horak, Peter; Le Tourneau, C.; et al. (Annals of oncology, 2025)
Background - With an increased uptake of genomic profiling in clinical practice and the evolving complexity of diagnostic modalities, vast amounts of complex data need to be properly interpreted and integrated into an individualised care plan. To address these challenges, molecular tumour boards (MTBs) have been widely established. As of today, no international recommendations regulating the composition and workflows of MTBs have been defined. - Methods - ESMO’s Precision Oncology Working Group (POWG) established an international expert panel in precision oncology and defined core areas of interest. After several consultations and through an expert consensus process, the group reached a consensus level for each recommendation. - Results - The group defined five components in the MTB process that are critical to its function and clinical use: (i) the primary task of MTBs consists in providing genomic-informed clinical recommendations, particularly for cases exhibiting complex genomic alterations; (ii) to achieve this, MTBs should encompass interdisciplinary expertise, with key roles for oncologists with genomic expertise, pathologists with molecular training and clinical geneticists; (iii) MTBs’ recommendations should be documented in a structured report that includes genomic-informed treatment strategies, management plans for potential tumour-detected germline alterations and guidance for additional genomic testing; (iv) structured follow-up processes should be implemented for monitoring the clinical effectiveness of MTBs recommendations and (v) finally, the panel proposed quality indicators for operating MTBs, including turnaround times for cases discussion and the proportion of cases for which actionable recommendations and clinical trial enrolments were successfully implemented. - Conclusions - These ESMO’s POWG recommendations can serve as a guidance and help to define quality standards for MTBs to allow for harmonisation and to further expedite the integration of precision oncology into clinical practice.
Online verfügbar: 6. April 2025, Artikelversion: 20. Mai 2025
Gesehen am 25.09.2025